An error resilient coding scheme for H.26L video transmission based on data embedding - Lin, Sheng-Wei; Leou, Jin-Jang; Kang, Li-Wei (Journal of visual communication and image representation, 2004)
For entropy-coded H.26L video frames, a transmission error in a codeword will not only affect the underlying codeword but also may affect subsequent codewords, resulting in a great degradation of the received video frames. In this study, an error resilient coding scheme for H.26L video transmission based on data embedding is proposed. At the encoder, for an H.26L intra-coded I frame, the important data for each macroblock are extracted and embedded into another macroblock(s) within the I frame and the next P frame by the proposed odd–even data embedding scheme. For an H.26L inter-coded P frame, the important data for each slice are extracted and embedded into the next frame by the proposed slice-based embedding scheme for P frames. At the decoder, for each corrupted macroblock, if the important data for a corrupted macroblock can be correctly extracted, the extracted important data will facilitate the employed error concealment scheme to conceal the corrupted macroblock. Otherwise, the employed error concealment scheme is used to conceal the corrupted macroblock. Based on the simulation results, the proposed scheme can recover high-quality H.26L video frames from the corresponding corrupted video frames up to a video packet loss rate of 30%.